Awareness of contact lens complications among contact lens users in UiTM Puncak Alam Campus / Nur Syafirah Zalaiqah Ruslan - Ruslan, Nur Syafirah Zalaiqah (2016)
Background: Contact lens wear has become a trend recently. It enhances one’s physical appearance without the need of glasses and boost self-confidence. However, improper usage of contact lens with insufficient hygienic of lens care may lead to serious vision-threatening complications. Purpose: This research was conducted to assess the level of awareness of contact lens complications among contact lens users in UiTM Puncak Alam Campus. Methods: This is a cross-sectional descriptive study. 60 regular contact lens users from UiTM Puncak Alam Campus were identified and enquired about the awareness of contact lens complications through a structured questionnaire. The questionnaire also asked regarding risk factors and knowledge of contact lens complications. Results: 60 regular contact lens users which were 57 female and 3 male participants had completed the questionnaire. The average age was 22.38 years. There was lack level of awareness assessed regarding the contact lens complications. The highest awareness of complication was allergy (45%) followed by corneal ulcer (41.7%), conjunctivitis (40%), corneal vascularization (28.3%), corneal opacities (26.7%) and corneal distortion (25%). Majority of the participants aware of the risk factors of contact lens complications but their knowledge was significantly low. Conclusion: Significant number of regular contact lens users in UiTM Puncak Alam Campus did not aware and know about contact lens complications. However, there was high awareness of risk factors of contact lens complications. In the future, more exposure and continuous contact lens education needed to be enhanced among the contact lens users in UiTM Puncak Alam Campus.